The synergistic effects of short inter-pregnancy interval and micronutrients deficiency on third-trimester depression - Lin, Jing; Zhou, Ye; Gu, Wei (Frontiers in Nutrition, 2022)
Objective: To explore the effect of inter-pregnancy interval (IPI) and micronutrients on depression in the third trimester of pregnancy. Methods: A total of 5951 eligible pregnant women were included in this single center retrospective cohort study. Variables with potential effects on third trimester depression were collected. These variables included: maternal factors (age, pregnancy interval, body mass index (BMI), BMI change, gravidity, native place, education, smoking, alcohol consumption), previous delivery outcomes (preterm birth, preeclampsia, intrahepatic cholestasis of pregnancy (ICP), gestational diabetes mellitus (GDM), fetal growth restriction (FGR), delivery mode), and micronutrients in early pregnancy (folic acid, 25-hydroxy vitamin D, vitamin B12, calcium and ferritin). Univariate and multivariate analysis were used to screen the factors affecting the occurrence of depression. Based on these factors, nomogram model was established. At the same time, the interaction between IPI and micronutrients was verified. Results: The incidence of depression in the third trimester of pregnancy was 4.3%. Univariate and multivariate analysis showed that there were five independent risk factors for third-trimester depression: gravidity, previous cesarean section delivery, folic acid and vitamin D levels in early pregnancy and IPI. According to the multivariate logistic regression analysis, the prediction model and nomogram were established. The prediction cut-offs of the corresponding factors were calculated according to the Youden index. Finally, the synergistic effect of short IPI and micronutrients deficiency was verified. Conclusion: There is a synergistic effect between short IPI and micronutrients deficiency in early pregnancy, which can aggravate the occurrence of depression in late pregnancy.